DEVELOPMENT AND EVALUATION OF AN INTEGRATED READING COMPREHENSION PROGRAM - Osoteo, Ciza Rhea (International Journal of Arts, Sciences and Education, 2021)
In Mallig Plains National High School, the students of Grade 10 Emerald have difficulty in understanding their lessons in English. They also have difficulty in examining textual details that affirm or refute a claim. Further, the researcher has observed that a number of them can recognize words in printed materials but still have difficulties in getting the implicit information in the printed material read. This problem on reading was evidently mirrored in the poor results of their exams in subjects where English is the medium of instruction. The above context propelled the researcher to conduct a study that aimed to address these reading problems. Through the instructional support materials in reading, it could address the reading comprehension of the G10 Emerald students of Mallig Plains National High School.This instructional support material in reading has focused on (RC) Reading Comprehension and integrates the six sub skills of reading. The participants of this study were five teachers and five students who were interviewed for the problems/challenges in teaching reading comprehension. The whole section of G10 Emerald has undergone the eight sessions using the instructional support material in reading. In summary, all the recommendations gathered under the instructional support materials in reading were encapsulated and served as basis for a Proposed Learning Continuity Plan of Mallig Plains National High School.